Pengembangan Media WordPress dalam Pengajaran Kosakata pada Siswa Tunanetra di Yayasan Raudlatul Makfufin Serpong - Huda, Ariqah Fairuz; Wahab, Muhbib Abdul; Susiawati, Wati (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2025)
This study aims to develop a WordPress-based learning media, namely HayyaNabda.my.id, designed to support vocabulary learning for visually impaired students. The media leverages screen reader features that are user-friendly for individuals with visual impairments. At the foundation, visually impaired students learn the rules of sharf and nahwu through singing methods to memorize tashrif and practice simple conversations. However, the lack of learning resources, such as limited Braille textbooks and only 60 minutes of weekly study time, forces teachers to rely more on lecture and conversational methods. While this approach facilitates material delivery, students still face difficulties in understanding vocabulary due to limited direct interaction and access to learning materials. Therefore, inclusive, comprehensive, and accessible learning media are needed to enhance students’ understanding of Arabic vocabulary. This research adopts the Research and Development (R&D) method with the ADDIE approach (Analysis, Design, Development, Implementation, Evaluation). The results of the study show that the use of WordPress-based media is effective in improving students' understanding of Arabic vocabulary. Media validation by material and media experts yielded excellent results, each scoring 88%. Meanwhile, pre-test and post-test results indicated an increase in the average student comprehension score from 88 to 95.14, with an N-Gain value of 0.62, categorized as "moderate." Based on these findings, WordPress is considered an inclusive, effective, and relevant learning medium to support Arabic vocabulary learning for visually impaired students, while also opening opportunities for further development in other special education institutions.